Trends in incidence and mortality of chronic obstructive pulmonary disease among residents of Xiamen city from 2012 to 2022: analysis of hospital records and death registration data - Youlan CHEN; Ahua WU; Moliang CHEN; Yilan LIN; Yanqi LAN; Qun LOU; Zhinan GUO (Zhongguo gonggong weisheng)
ObjectiveTo analyze the trends in incidence and mortality of chronic obstructive pulmonary disease (COPD) among residents of Xiamen city, Fujian province from 2012 to 2022, and to provide a reference for the prevention and control of COPD in the population. MethodsPersonal medical records of COPD patients, who visited any medical and health institutions in Xiamen city from 2012 to 2022, were extracted from the Xiamen City Health and Medical Big Data Information Platform. The collected COPD mortality data were matched with records in the city′s death registration management system. Crude and standardized rates of COPD incidence and mortality were calculated. Joinpoint model was used to calculate the annual percentage change (APC) and average annual percentage change (AAPC) of COPD incidence and mortality from 2012 to 2022. ResultsFor the city residents from 2012 to 2022, the annual crude incidence rates (1/100 000) of COPD were 162.69,187.90, 220.63, 230.48, 282.77, 268.19, 296.16, 349.67,199.05, 213.45, and 245.41 and the annual standardized incidence rates (1/100 000) of COPD were 140.63, 167.88, 218.19, 223.58, 276.87, 266.70, 295.78, 343.48, 190.35, 208.62, and 240.19, respectively. There were no significant changing trends observed in both crude and standardized incidence rate of COPD during the whole period (both P > 0.05), but both the crude incidence rate (APC = 10.44%, t = 2.57; P = 0.042) from 2012 to 2018 and the standardized incidence rate (APC = 15.58%, t = 2.76; P = 0.033) from 2012 to 2017 showed an increasing trend. During the study period, the annual crude mortality rates (1/100 000) for COPD were 14.47, 16.19, 19.77, 24.66, 30.42, 33.05, 36.30, 38.39, 34.08, 40.37, and 45. 37 and the annual standardized mortality rates (1/100 000) of COPD were 14.74, 16.46, 19.07, 22.79, 28.23, 31.87, 35.16, 36.33, 30.75, 37.70, and 41.39, respectively; both the crude mortality rate (AAPC = 12.20%, t = 7.6, P < 0. 001) and the standardized mortality rate (AAPC = 10.60%, t = 5.7, P < 0.001) showed a significant increasing trend; further subgroup analysis showed that the increasing trend of the crude COPD mortality rate was significant for male and female residents and for residents aged 60 – 69, 70 – 79, and ≥ 80 years (all P < 0.05), and the increasing trend of standardized COPD mortality rate was significant for both male and female residents (both P < 0.05). ConclusionAmong the residents of Xiamen city, the COPD incidence rate from 2012 to 2018 and the standardized incidence rate of COPD from 2012 to 2017 showed an increasing trend; the crude and standardized mortality rates of COPD also showed an increasing trend from 2012 to 2022.